2015
DOI: 10.4172/2161-1122.1000324
|View full text |Cite
|
Sign up to set email alerts
|

Root Morphology and Tooth Length of Maxillary First Premolar in Nepalese Population

Abstract: routine orthodontic procedure in Dhulikhel Hospital, Kathmandu University School of Medical Sciences are collected for the study. The tooth immediately after extraction is rinsed with water to clean the blood debris then dipped into 5.2% Sodium Hypochlorite solution for two minutes and stored in 10% formalin until measurements are done. While collecting the teeth, male and female teeth are collected in a separate collection bottles with clearly written labels. Verbal consent is obtained from patient to keep th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 10 publications
3
1
0
Order By: Relevance
“…A few publications on tooth anatomy have discussed the relationship between root structure and sex [24,[29][30][31]. No statistically significant difference in the number of roots in the teeth of women and men was found in the present study, which is consistent with the results obtained from Spanish [24], Turkish [29], and Nepalese [30] populations.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…A few publications on tooth anatomy have discussed the relationship between root structure and sex [24,[29][30][31]. No statistically significant difference in the number of roots in the teeth of women and men was found in the present study, which is consistent with the results obtained from Spanish [24], Turkish [29], and Nepalese [30] populations.…”
Section: Discussionsupporting
confidence: 91%
“…A few publications on tooth anatomy have discussed the relationship between root structure and sex [24,[29][30][31]. No statistically significant difference in the number of roots in the teeth of women and men was found in the present study, which is consistent with the results obtained from Spanish [24], Turkish [29], and Nepalese [30] populations. However, in a Chinese population, double-rooted teeth were twice as common in men (62.68%) than women (33.33%), and threerooted teeth were observed in 3.73% of teeth from men, but were absent from women (0%) [31].…”
Section: Discussionsupporting
confidence: 91%
“…Despite, males displaying generally larger dentition than females, very weak correlations between each morphometric parameter and sex were recorded in this study. This corroborated the findings of previous studies, who also reported dentition in males [3][4][5][6][7]. Moreover, the South African Black population group also displayed larger tooth dimensions than the South African Indian population group in this study.…”
Section: Discussionsupporting
confidence: 93%
“…Sexual dimorphism refers to differences in the physical appearance, size and stature between males and females [3]. Subsequently, this also applies to the shape and size of dentition, which varies between the sexes, with males generally displaying greater tooth dimensions than females [3][4][5][6][7]. Sex determination plays an integral role in the biological profiling of unidentified remains, and often forms the foundation for subsequent profiling, viz.…”
Section: Introductionmentioning
confidence: 99%